Case Study: Developing, Implementing, and Evaluating a One-Day Leadership Conference to Foster Women's Leadership in Healthcare - Kerry K. Fierke; Margarette L. Kading (University of Minnesota Libraries Publishing, 2014)
Despite women increasingly entering the healthcare field, they still face barriers to advancing in leadership ranks within healthcare. To address the need for leadership development among women in healthcare, the Center for Leading Healthcare Change (CLHC) at the University of Minnesota College of Pharmacy piloted a one-day conference in November 2012 entitled "Women Impacting Healthcare: Decide to Make a Difference." This conference utilized an interactive agenda: each speaker's presentation was followed by hands-on leadership activities during which attendees developed their own personal leadership visions. Specific leadership activities were designed to build upon one another and help design a leadership pathway. All activities were consistent as they included personal reflection and interaction with others. Attendees were asked to complete two evaluations, one immediately at the conclusion of the conference, and another two-weeks post. The conference committee achieved the goal of delivering the conference objectives. As the Women Impacting Healthcare committee continues to look for ways to develop leaders in healthcare, the focus of future conferences will also evolve to include the needs of women currently in leadership roles, as well as ways women can grow into leadership roles.   Type: Case Study